Proposal of ecological rehabilitation of degraded site in the coastal band of the Biosphere Reserve Baconao - Edelyn Robert Kernizan; Eduardo González-Izquierdo; Luz Margarita Figueredo Carmona (Revista Cubana de Ciencias Forestales, 2013)
The work was carried out in the southeast coast of Cuba, in the 19º 54' of North latitude and 75º 28' of longitude West, at a distance of 46 Km., to the east of the city of Santiago de Cuba, inside the Baconao Biosphere Reserve, between the Restaurant «La Jaiba Azul» and the entrance to Baconao Lagoon, and in Category 2 according to the UICN System of Category. The objective of the research is: To propose actions for the ecological rehabilitation in the coastal band of Baconao. 13 parcels of 10 x 20 m were mounted, in the East, Centre and West of the study area. All the observed species were written down and those that could not be easily identified were collected in the site. The main problems were identified in the study area. It was carried out a series of assessments about the factors that have impacted in the degradation of the vegetation among which stands out the high anthropization degree. They main actions that will allow the rehabilitation of the area were proposed with prevalence of reforestation with native species from coastal band of Santiago de Cuba that can be considered as effective. This aspect, the increase of the natural populations of the typical species of the vegetation complex in this coastal area and the increment of their forest covering, are the first signs of the rehabilitation process.